Organizational Culture on Knowledge Sharing: Literature Review - Tri Wahyudi; Muhamad Septian Nurafan; Zain Fuadi Muhammad RoziqiFath; Jun Surjanti; Dewie Tri Wijayati Wardoyo; Arina Salsabilla Haq (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: This research investigates the influence of organizational culture on knowledge sharing practices through a Systematic Literature Review (SLR) approach that follows strict protocols to minimize bias. Method: The SLR process began with a literature search using Harzing's Publish or Perish on Google Scholar, Semantic Scholar, and Scopus databases with the keywords “organizational culture”, “corporate culture”, “knowledge sharing”, “knowledge exchange”, and “knowledge transfer”, resulting in 320 initial articles (2019-2025). Inclusion criteria included English/Indonesian articles that presented empirical evidence on the causal relationship between organizational culture and knowledge sharing, while opinion articles, non-full text, and studies without explicit analysis were excluded. After a three-stage selection (title screening, abstract screening, full-text assessment), 78 articles were eligible for thematic analysis using NVivo 12. The main themes identified include: (1) the dominance of the collaborative culture dimension in facilitating knowledge sharing, (2) the ambivalent role of authoritarian leadership as both an obstacle and a driver of knowledge exchange efficiency, (3) technological literacy inequality as a critical moderator, and (4) the dynamics of knowledge hoarding in hierarchical organizations. Results: The analysis shows that 65% of the studies are concentrated on the corporate sector, while NGO and public service contexts account for only 12%. The main limitations lie in the methodological heterogeneity of the reviewed studies (65% quantitative, 28% qualitative, 7% mixed) and geographical bias (82% of studies from Asia and Europe). Novelty: Nevertheless, the synthesis of findings reveals a pattern that an organizational culture based on psychological safety and a non-monetary incentive system increases the intensity of knowledge sharing by 40%. This study recommends an integrative framework that combines Resource-Based View and Social Exchange theories for future studies.